Skeletal, Dentoalveolar and Soft tissue Components of Skeletal Class II Malocclusion among Nepalese Orthodontic Patients: A Cephalometric Study - Shrestha, Raju; Halwai, Hemant Kumar; Yadav, Sumit Kumar; Gupta, Sandeep Kumar (Orthodontic Journal of Nepal, 2022)
Introduction: The understanding of the craniofacial morphology of skeletal Class II malocclusion is a key element in planning orthodontic treatment. The aim of this study was to describe various skeletal, dentoalveolar, and soft tissue components of skeletal Class II malocclusion in Nepalese orthodontic patients. Materials and Method: This cross-sectional study was carried out at the Universal College of Medical Sciences (UCMS) in the Department of Orthodontics and Dentofacial Orthopedics. Lateral cephalograms of 70 patients with skeletal class II malocclusion of age greater than 1 8 years, and ANB > 4°, were traced. Various skeletal, dentoalveolar, and soft tissue measurements were taken. Descriptive statistics were performed followed by an independent sample t-test to find the difference in mean of various cephalometric parameters between males and females. Result: Among 70 subjects, 54 samples had class II div 1 malocclusion and 16 had class II div 2 malocclusion. Mandibular retrognathism was seen in 37 subjects having skeletal Class II Div 1 malocclusion and in 9 subjects with Class II Div 2 malocclusion. The mean value of SNA was 82.91 ° ± 2.87°, SNB was 76.81 ° ± 2.97°, and ANB was 6.11 ° ± 1.22° in Class II Div 1 subjects. In subjects with Class II Div 2, the mean value of SNA was 82.31 ° ± 3.19°, SNB was 76° ± 4.08°, and ANB was 5.44° ± 1.21 °. Mean value of U1 to NA degree and linear measurement was Class II div 1 was 28.30° ± 6.86° degree and 5.56 ± 2.76 mm respectively. Similarly, mean value of LI to NA degree and linear measurement was 31 .93° ± 5.96° and 6.16 ± 2.37 mm respectively. Mean and standard deviation value of upper lip to S-line and lower lip to S-line was 2.85 ± 2.1 3 mm and 3.54 ± 2.47 mm respectively in Class II Div 1 subjects. Similarly, in Class II Div 2 it was 1.50 ± 2.16 mm and 0.13 ± 2.66 mm respectively. Mean and standard deviation value of nasolabial angle was 93.69° ± 12.91° in Class II div 1 and 96.38° ± 12.26° degree in Class II Div 2. The mean values of most cephalometric parameters did not differ statistically between male and female subjects with Class II div 1 malocclusion. Conclusion: In subjects with skeletal Class II mean value of SNA was within normal range whereas SNB was decreased. Retrognathia and a small mandible in relation to the cranial base with a well-positioned maxilla were observed in the majority of subjects. Mean U1 to NA angular and linear measurement was increased in Class II Div 1, whereas they were decreased in Class II Div 2.